Pengaruh Tipe Kepemimpinan Kepala Sekolah dan Pemberian Stimulus Kerja terhadap Kinerja Guru pada Smk Wira Buana Bekasi - Chandra S. Haratua; Arie Budiyanti; Endang Setyowati; Fadli Novrianda; Meti Milawati (Attractive : Innovative Education Journal, 2024)
Leadership style and the ability to motivate teachers are two aspects of school human resource management that are closely connected. Because of its impact on educator effectiveness, this merits consideration in plans for the future of education. Educators, in their role as creators of a conducive learning environment, have a responsibility to support their students' intellectual growth by challenging them to think critically and imaginatively. A good leadership style is context dependent; this is especially true for school principals, who are required to cultivate a dynamic leadership style. At the Wira Buana Bekasi Vocational School, the research was conducted. Finding out how principal leadership style and offering work motivation affect teachers' performance is the main goal of this research. Thirty instructors from Wira Buana Bekasi Vocational School participated in the survey that formed the basis of this study. Leadership style, offering job incentive, and instructor performance are the three facets of the data gathering approach that utilize primary data and are collected through interviews, observations, and surveys. The outcomes indicate that the administration style of the principal and the availability of work incentive significantly impact teacher performance in a good way. Results from data analysis employing partial and multiple correlation approaches, multiple regression, and followed by hypothesis testing provide support for this, as does the Y a decrease equation = 14.400 + 0.498 X1 + 0.232 X2. The r2 coefficient is 68%.